Letter to library from the American Library Association (Raton, NM, 1920)
Letter to library from the American Library Association about books for everybody in every state of the union. , May 25, 1920
1 page typed letter to the American Library Association by Evlyn Shuler
Master list item #: 15
File location is in the Raton File Cabinet drawer 3
Keywords: Shuler, Evlyn -- Librarian -- Raton, New Mexico; Library. -- New Mexico; Letter -- Raton, New Mexico; American Library Association